The effects of household income composition on food consumption in Malawi - Benfica, Rui (Africa Scholarly Science Communications Trust, 2023)
This analysis uses panel data methods to assess how food consumption and dietary diversity are affected by changes in household income composition, diversity, and liquidity in rural Malawi. Fixed-effects model estimates reveal several results. First, food consumption and dietary diversity increase with overall income, but at a decreasing rate. Second, while no relationship is found between changes in income per capita of different sources (composition effects), and food consumption per capita, there is a differentiated impact on calorie intake changes and dietary diversity outcomes. Third, overall, there is no statistically significant effect of income diversity on changes in food consumption, but a positive association is found with dietary diversity. As such, income diversity driven by crop diversification leads to greater consumption of calories from roots, pulses, and fruits; and a drop in balanced diets, while income diversification away from agriculture yields greater dietary diversity. Finally, household liquidity, incentivized by off-farm diversification through wage labor market participation and selfemployment, promotes dietary diversity via higher consumption of calories from non-staple foods, notably those dependent on market acquisitions, such as animalbased proteins, vegetables, and fruits. These results are corroborated with those from the Seemingly Unrelated Regression Model. There are several policy and programmatic implications. First, income composition, diversity and liquidity are important dimensions to consider when focusing beyond household food security. Second, efforts to promote and sustain income growth are critical for food consumption growth and dietary diversity but increases in income alone are not enough. Policies and investments that ensure a diversified portfolio of economic activities are likely to result in better consumption and dietary diversity outcomes. Promoting crop diversification at the farm level coupled with nutrition sensitive programming, including extension and crop support programs is critical to increase and sustain consumption and better dietary quality. Third, as balanced diets in the Malawian context require a combination of staple foods sourced through crop and livestock home production, including goats, poultry and small domestically raised animals and protein-rich foods typically purchased in the market, as well as a degree of liquidity achieved through increased generation of cash income. Finally, programmatic efforts are needed to reduce gender gaps in access to resources, strengthening nutrition education more broadly, and ensure availability of balanced diets in school feeding programs potentially linked through local procurement.